PENGARUH MODEL PEMBELAJARAN POINT COUNTER POINT (PCP) BERBANTUAN MEDIA SOSIAL INSTAGRAM TERHADAP KETERAMPILAN MENULIS TEKS ARGUMENTASI SISWA KELAS XI - Khadavi; Wisman Hadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to (1) Analyze argumentative writing skills without using the Point Counter Point (PCP) learning model assisted by Instagram social media for class XI students of SMA Negeri 1 Kisaran, (2) Analyze argumentative text writing skills using the Point Counter Point (PCP) learning model assisted by Instagram social media for class XI students of SMA Negeri 1 Kisaran, (3) Analyze the effect of using the Point Counter Point (PCP) learning model assisted by social media on writing argumentative texts for class XI students of SMA Negeri 1 Kisaran. This study involved all 357 class XI students of SMA Negeri 1 Kisaran, with a sample of 72 people divided into two classes: the control class (36 people) and the experimental class (36 people). The assessment instruments used included the introduction, the content (argument body), the closing, denotative sentences, verbs, adverbs, and conjunctions. The experimental method used was a two-group post-test design with a quantitative approach, and used data analysis techniques such as analysis requirements tests, normality tests, homogeneity tests, and hypothesis tests. The results of the study showed that the skill of writing argumentative texts using the Point Counter Point (PCP) learning model assisted by Instagram social media had a significant impact, as evidenced by the tcount value > ttable, namely 7.5703 > 2.03224, indicating a significant influence on the skill of writing argumentative texts of class XI students of SMA Negeri 1 Kisaran.